A new approach for the vanishing gradient problem on sigmoid activation - Roodschild, Matías; Gotay Sardiñas, Jorge; Will, Adrián (Progress in artificial intelligence, 2020)
The vanishing gradient problem (VGP) is an important issue at training time on multilayer neural networks using the backpropagation algorithm. This problem is worse when sigmoid transfer functions are used, in a network with many hidden layers. However, the sigmoid function is very important in several architectures such as recurrent neural networks and autoencoders, where the VGP might also appear. In this article, we propose a modification of the backpropagation algorithm for the sigmoid neurons training. It consists of adding a small constant to the calculation of the sigmoid’s derivative so that the proposed training direction differs slightly from the gradient while keeping the original sigmoid function in the network. This approach suggests that the derivative’s modification produces the same accuracy in fewer training steps on most datasets. Moreover, due to VGP, the original derivative does not converge using sigmoid functions on more than five hidden layers. However, the modification allows backpropagation to train two extra hidden layers in feedforward neural networks.